Knowledge management establishment for supporting disaster response with offline web application - Tumer, Erdal Taner (My University, 2010)
BAĞLANTISIZ WEB UYGULAMALARININ FELAKETLERE MÜDAHALEDE BİLGİ YÖNETİMİNDE KULLANILMASI Deprem, sel , su taşkınları, kargaşa ve savaş gibi felaket durumlarında insani yardımda bulunan ekiplerin koordinasyonu için sağlıklı bir şekilde bilgi paylaşımına ihtiyaç duyulmaktadır. Yaptığımız bu çalışmada insani yardım ekiplerinin sağlıklı bir şekilde bilgi paylaşabilecekleri her Bilgi Yönetim Sisteminde olması gereken düşük kalitedeki ağ bağlantısı üzerinden veri aktarımı özelliğini sağlayacak bir yapı oluşturmayı amaçladık. Önerilen sistem internet teknolojilerine bağlantısız (offline) çalışma yeteneği kazandırarak güvenilir bir bilgi paylaşım ortamı sağlamayı amaçlamaktadır. Genel olarak kullanıcı tabanlı uygulamalarla kıyasladığında, internet uygulamaları pek çok farklı aktörden ve platformdan bilgi toplama konusunda avantajlara sahip olmaktadır, fakat güvenilir bir ağ bağlantısının olmadığı durumlarda internet uygulamaları bilgi aktarımı ödevlerini yerine getirememektedir. Alt yapının ciddi bir şekilde etkilendiği felaket ortamlarıda bu şekilde sağlıklı bir ağ bağlatısının sağlanamadığı ortamlardır. Yapılan çalışmayla internet teknolojilerine bağlantısız çalışabilme özelliği kazandırılarak Türk Kızılay’ı, AKUT, NATO, Ordu ve benzeri yardım kuruluşlarının kullandığı sistemlere “güvenilir bir veri paylaşım” özelliği kazandıracak bir yapı oluşturulmaya çalışıldı. XML paket sıkıştırma, öncelikli paket transferi ve web servis tekniklerini kullanarak oluşturulan çözüm, yapılan testlerde %50 ye kadar paket kaybının yaşandığı 28.8 ve 56 kbps hızlarına sahip düşük kaliteli bağlantılarda beklenilen sonuçlar elde edilmiştir. Böylelikle tüm verilerin bu bağlantı üzerinden aktarımı sağlanmıştır.

KNOWLEDGE MANAGEMENT ESTABLISHMENT FOR SUPPORTING DISASTER RESPONSE WITH OFFLINE WEB APPLICATION During the response to disaster situations such as earthquake, flood, military conflicts and riots it is necessary to collect information as soon as possible in order to coordinate response. This study aimed to provide a reliable framework for any Disaster Knowledge Management System that operates on disaster conditions and requires provision of reliable data transfer functionality over low quality networks. By using web technologies and a web tool with offline capacities the framework would assist the response teams for their data collection and sharing needs. Web tools could provide many advantages to collect this from many different actors, compared to client installed solutions. However in disaster environments web tools can not be used because they are depended on availability of the network connectivity and one of the many facilities that are usually lacking in the field in emergencies, particularly in the disaster areas where infrastructure has been affected, is network connectivity. In general reliable and persistent Internet connection can not be present in these environments. By introducing offline capabilities to the web technologies, this framework would provide a working solution that can operate on low quality networks. Project will also provide a prototype application which implements the framework that simulates the disaster response and aid system used by organizations such as Turkish Red Crescent, AKUT, NATO, Military and others. The solution offered in this project uses XML compression and packet prioritization and based on open source web technologies. The experiments done in the test environment provide promising results on the low quality networks where the bandwidth is 28.8 kbps and 50% packet loss occurred, the framework successfully transfer all the information where direct data transfer failed.
Keywords: Bilgi Yönetimi; Bilgisayar Mühendisliği